Classification of nighttime light types in China’s nature protected areas based on SDGSAT-1 - Yangyang Yan; Rong Zhang; Zongming Wang; Chuanpeng Zhao; Haihang Zeng; Qian Shi; Mingming Jia (International Journal of Digital Earth)
Protected areas play a crucial role in preserving biodiversity and providing ecosystem services. However, the encroachment of nighttime light increasingly exacerbates light pollution in these regions. Previous studies using remote sensing to assess light pollution in protected areas have primarily relied on single-band Nighttime Light (NTL) imagery, failing to account for the varying impacts of different types of NTL. To address this gap, this study developed a classification method using multispectral NTL data from the SDGSAT-1 Glimmer Imager, classifying NTL types and quantifying their distribution in and around protected areas. The results are as follows: (1) The majority voting method achieved an overall accuracy of 96.97% and a Kappa coefficient of 0.94, surpassing single methods. (2) Among 85 protected areas in China, LED lights covered 1759.05 km² with a radiance sum of 64310.19 W/(sr·m²), while other lights covered 1765.99 km² with a radiance sum of 40904.86 W/(sr·m²). (3) In 42 protected areas, the proportion of LED lights was higher than other lights, and 57 protected areas exhibited higher average pixel radiance from LED lights. The methods and findings provide data for assessing and managing light pollution in China's protected areas, aiding in formulating sound conservation strategies and promoting sustainable development.